1995
DOI: 10.1097/00005392-199501000-00046
|View full text |Cite
|
Sign up to set email alerts
|

Myelolipoma of the Adrenal Gland Associated With Contralateral Renal Cell Carcinoma: Case Report and Review of the Literature

Abstract: Adrenal myelolipoma is a rare benign hormonally inactive tumor. It is frequently detected incidentally on new imaging procedures, such as sonography and computerized tomography and, thus, the question of treatment arises. The association of myelolipomas with obesity, hypertension and malignant tumors has been described previously. We report the second case of myelolipoma associated with renal cell carcinoma. Pathogenesis, differential diagnosis and therapy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
1
19
0
2
Order By: Relevance
“…5 cm and weighed 225 g. This is probably the largest adrenal lipoma reported. CT scan revealed an extrarenal encapsulated mass with a tissue density equivalent to fat and radiologically differential diagnosis included myelolipoma, retroperitoneal liposarcoma and angiomyolipoma of the kidney [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…5 cm and weighed 225 g. This is probably the largest adrenal lipoma reported. CT scan revealed an extrarenal encapsulated mass with a tissue density equivalent to fat and radiologically differential diagnosis included myelolipoma, retroperitoneal liposarcoma and angiomyolipoma of the kidney [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…25 Extra-adrenal endocrine dysfunction has been reported with myelolipomas, with rare cases of pituitary Cushing's disease, 20 adrenogenital syndrome associated with an interstitial tumour of the testis 26 and a case of hyperparathyroidism due to a parathyroid adenoma. 27 Moreover, myelolipomas are associated with extra-adrenal pathology, including different types of cancer such as oesophageal, 22 renal, 28 endometrial, 29 breast, 30 gastric 31 and small-cell lung cancer. 32 The exact pathogenesis of adrenal myelolipoma is unknown, but it appears plausible that multiple factors, including hormonal stimulation, are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal myelolipomas are rare benign tumors usually detected incidentally or at autopsy [4,5], Dieckman et al [6] in 1987 and Hofmockelet al [7] in 1995 reviewed the literature till 1991 and found only 70 surgically treated, well-documented cases of adrenal myelolipoma (includ ing 1 extra-adrenal case). The age ranged from 14 to 73 years and the majority were 50-60 years old.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 5 of our patients were symptomatic, and only in 1 case was the mass detected incidentally. The association of adrenal myelolipomas with obesity, hypertension, chronic diseases and malignancies like re nal cell carcinoma of the contralateral [7] or the same side [38], interstitial Leydig cell tumor [39], vaginal [40] or uri nary bladder carcinoma [6], adrenal adenoma [19], en dometrioid carcinoma [22], gastric adenocarcinoma [23], breast carcinoma [24] and pheochromocytoma [33] has been described in the literature. Our case 1 was obese, hypertensive and diabetic, whereas cases 5 and 6 were hypertensive only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation